SALINITY EFFECTS ON TRANSPIRATION IN EUCALYPTUS CAMALDULENSIS AND COMBRETUM QUADRANGULARE - Luangjame, Jesada (วารสารวนศาสตร์ไทย, 2022)
The aim of this study was to investigate the transpiration rates in two salt-tolerant tree species, Eucalyptus camaldulensis Dehnh. and Combretum quadrangulare Kurz. A greenhouse experiment with different levels of NaCI salinity (0, 0. 5, 1.0, 1.5 and 2.0%) was set up and the results were compared with those of a field study on non-saline and saline soils. In the greenhouse experiment, transpiration increased at low salinity but decreased at high salinity levels. Transpiration rates always increased with temperature. With irradiance they only increased up to medium photon flux density (up to 1500 µmol m-2s-1) and then decreased at 2000 µmol m-2s-1. In the field study, transpiration rates increased with temperature and irradiance in both species and they were much higher in E. camaldulensis than in C. quadrangulare. The relationships between transpiration rate, temperature and irradiance did not indicate any distinct effects caused by salinity. Key words: salinity, transpiration, water-use efficiency, Eucalyptus camaldulensis, Combretum quadrangulare.